Syn-Eruptive Processes During the January–February 2019 Ash-Rich Emissions Cycle at Mt. Etna (Italy): Implications for Petrological Monitoring of Volcanic Ash - D’Oriano, Claudia; Del Carlo, Paola; Andronico, Daniele; Cioni, Raffaello; Gabellini, Pietro; Cristaldi, Antonio; Pompilio, Massimo (Frontiers in Earth Science, 2022)
Formation of low-level plumes related to low intensity ash-rich emissions has increasingly become a common type of activity at Mt. Etna (Italy), and, in January-February 2019, it occurred with high frequency from the Northeast Crater. The onset of this activity was preceded on 24 December 2018 by a powerful Strombolian eruption from a fissure opened at the base of the New Southeast Crater, accompanied by a lava flow from the same fissure and by an ash-rich plume, 8-9 km high a.s.l., from the crater Bocca Nuova. On 27 December 2018, the lava effusion cessation was signed by the resumption of intra-crater Strombolian and sustained degassing activities from Bocca Nuova and Northeast Crater, lasting about 4 weeks. On 23 January 2019, an eruptive cycle of ash-rich emissions started, mainly issued from the Northeast Crater. The activity was characterized by the emission of fine-grained material forming weak plumes up to 1 km above the crater, rapidly dispersed towards different directions by dominant winds and recorded up to a distance of 30 km from the vent. This activity oscillated from pulsating to continuous for one month, with a mean frequency of one episode per week, with the more intense phases lasted for a few hours. Studied samples record the whole spectrum of eruption styles occurred in the period between 24 December 2018 and 20 February 2019. Quantitative analyses include grain size, ash componentry and morphology, microlites size distribution and glasses and minerals compositions. Results highlight the difficulty to discriminate between juvenile and not-juvenile ash components in this type of eruptions, and also, among the juvenile material, a large variability of textural and compositional features, both at the scale of each sample and all along the eruptive cycle. We propose that the low amount of juvenile ash results from episodic ascent of small magma batches from shallow reservoirs, travelling within a slow rising magma column subjected to cooling, degassing and crystallization. The large number of recycled clasts, deriving from a thick layer of variably sealed or thermally altered material at the top of the magma column, is suggested to contribute to the ash generation.